2019
DOI: 10.1097/fbp.0000000000000466
|View full text |Cite
|
Sign up to set email alerts
|

Early-life stress influences acute and sensitized responses of adult mice to cocaine by interacting with GABAA α2 receptor expression

Abstract: N (2019) Early life stress influences acute and sensitised responses of adult mice to cocaine by interacting with GABAA α2 receptor expression. Behavioural Pharmacology, 30 (2-3). pp. 272-281.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…In cocaine-dependent individuals, GABRA2 SNPs were associated with cocaine cue reactivity ( 192 ). The involvement of α2GABAARs in some, but not all, effects of cocaine has also been confirmed in rodent studies ( 191 , 193 , 194 ). Finally, long-term exposure to cocaine was found to cause changes in the expression of α2GABAARs in the hippocampi of rodents ( 195 ), however, this finding was not confirmed in postmortem studies of hippocampi from individuals with cocaine use disorder ( 187 ).…”
Section: Gabaars In Alcohol and Other Substance Use Disordersmentioning
confidence: 63%
“…In cocaine-dependent individuals, GABRA2 SNPs were associated with cocaine cue reactivity ( 192 ). The involvement of α2GABAARs in some, but not all, effects of cocaine has also been confirmed in rodent studies ( 191 , 193 , 194 ). Finally, long-term exposure to cocaine was found to cause changes in the expression of α2GABAARs in the hippocampi of rodents ( 195 ), however, this finding was not confirmed in postmortem studies of hippocampi from individuals with cocaine use disorder ( 187 ).…”
Section: Gabaars In Alcohol and Other Substance Use Disordersmentioning
confidence: 63%
“…In rodents, maternal separation (MS) with early weaning (MSEW) is a reliable animal model of ELS and depression‐like behaviour 6‐8 . Other studies have reported changes in brain‐derived neurotrophic factor (BDNF) expression in the hippocampus, ventral tegmental area (VTA), and prefrontal cortex of maternally separated rats 9 . Moreover, increased BDNF in the VTA of rats induces a higher vulnerability to drug abuse, turning the GABA inhibitory system to excitatory signalization 10 …”
Section: Introductionmentioning
confidence: 99%